Effect of palm oil based microcrystalline cellulose on properties of acrylic denture base resins / Amira Ali Abdel Rahaman Ali - Amira Ali, Abdel Rahaman Ali (2017)
The objective of this study was to assess whether the reinforcing of acrylic denture base resin poly methyl methacrylate (PMMA) with oil palm based microcrystalline cellulose (MCC) has an impact on the flexural properties in addition to studying the biocompatibility, chemical and microstructure of the resultant composite (PMMAMCC). For the purpose of flexural strength and flexural modulus evaluation, three MCC reinforced PMMA groups were fabricated and compared with the conventional and commercially available PMMA. The three test groups were represented by addition of MCC by 2% (+ equal amount of MMA liquid increased) only, 2% (+ equal amount of PMMA powder reduced) and 5% (+ equal amount of PMMA powder reduced)respectively. Twenty specimens (65 mm x 10 mm x3 mm) for each group were prepared according to the manufacturer instructions. In addition to the establishment of cytotoxicity, fourier transform infra-red and scanning electron microscopy tests were also done. One-way analysis of variance (ANOVA) was used to determine statistical differences among the experimental groups. The three test groups with MCC addition demonstrated statistically significant differences in flexural strength and flexural modulus values compared to the conventional resin (P ≤ 0.05). The highest mean flexural strength was corresponding to the PMMA reinforced with 5% MCC followed by 2% MCC when compared to the conventional PMMA. The improvement in the flexural quality of a denture base acrylic material utilizing MCC supports the potential application of natural fibres in MCC form in the future fabrication of denture base resin. MCC of oil palm empty fruit bunch represents a viable alternative to the current commercially available synthetic reinforced acrylic denture base resin.